EASTERN PHILOSOPHY AND THE CONCEPT OF HOLISTIC HEALTH - Gadoyeva Lobar Ergashevna (Western European Studies, 2026)
This article explores the concept of holistic health through the lens of Eastern philosophy, focusing on traditions such as Taoism, Buddhism, and Ayurveda. Unlike the Western biomedical model, which often separates mind and body, Eastern philosophical systems view health as a dynamic balance between physical, mental, emotional, and spiritual dimensions of human existence. The paper examines key ideas such as harmony with nature, balance of energies, mindfulness, and ethical living as essential components of well-being. By analyzing classical philosophical concepts and their relevance to modern lifestyles, the article highlights how Eastern philosophy offers a holistic understanding of health that emphasizes prevention, self-awareness, and inner harmony rather than mere absence of disease.
Keywords: Eastern philosophy; mind-body unity; holistic health